STRATEGI PENINGKATAN KESEHATAN PRIMER: LANGKAH-LANGKAH MENUJU KETAHANAN KESEHATAN NASIONAL YANG BERKELANJUTAN - Latif Al Waroi, Muhammad Nur Abdul; Supriyadi, Imam (Yayasan Education and Social Center, 2024)
The Jaminan Kesehatan Nasional (JKN) scheme, launched in 2014, aimed to achieve universal health coverage in Indonesia by providing comprehensive healthcare services and reducing out-of-pocket expenses. Despite progress, challenges persist in the primary healthcare system, including disparities in access and quality between urban and rural areas, financial sustainability, and the need for continuous improvements in service delivery. This study employed a systematic literature review (SLR) methodology to evaluate the effectiveness and challenges of JKN in strengthening primary healthcare services, focusing on the period 2013–2024. The primary healthcare framework in Indonesia, centred around community health centres (Puskesmas), sub-district health centres (Pustu), and village health posts (Posyandu), plays a pivotal role in delivering accessible and comprehensive care. However, the unequal distribution of resources and inadequate training of healthcare providers remain significant obstacles. Recent reforms and initiatives aimed at strengthening the primary healthcare system have focused on improving access, quality, and sustainability through infrastructure enhancements, healthcare worker training, service integration, technology utilization, and community participation. The SLR process involves identifying research questions, conducting literature searches, selecting studies based on inclusion and exclusion criteria, extracting data, and synthesizing findings. The results of SLR are expected to provide insights into the effectiveness and challenges of JKN, forming a foundation for enhanced policy development within the national healthcare system. This study underscores the importance of comprehensive and sustainable strategies for strengthening primary healthcare to ensure the sustainability of JKN and equips policymakers and healthcare practitioners with evidence to strengthen the national healthcare system towards sustainable resilience